Fostering Student Motivation Through Teacher Competence - Ardiana Dyah Cahyanti; Budi Purwoko; Amrozi Khamidi; Nunuk Hariyati; Erny Roesminingsih (LP. Ma'arif Janggan Magetan, 2024)
Teacher competency is the teacher's ability to direct the student learning process in the classroom. Teachers have an important role for students both in the classroom and outside the classroom, therefore teacher competence in teaching is very important. Competence is behavior that is reasonable in order to achieve goals that were previously adjusted due to existing conditions so that competence can be interpreted as a skill and ability. Teachers have an important role to guide students in the learning process. The teacher's ability to design effective learning strategies, understand students' individual needs, and present material in an interesting way can influence students' motivation to learn. In participating in the learning process, each student's motivation is different, some are high and some are low, in this case the teacher must influence student motivation externally to form students' internal motivation. The aim of this research is to analyze teacher competence to increase student learning motivation. The method used is a literature study which focuses on research on teacher competency to increase student learning motivation. The results of the literature review regarding teacher competence to improve student learning can be achieved by increasing the existing competence of each teacher so that this goal is achieved optimally